2011
DOI: 10.1007/s11858-011-0326-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a learning trajectory for length in the early years

Abstract: Measurement is a critical component of mathematics education, but research on the learning and teaching of measurement is limited, especially compared to topics such as number and operations. To contribute to the establishment of a research base for instruction in measurement, we evaluated and refined a previously developed learning trajectory in early length measurement, focusing on the developmental progressions that provide cognitive

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
8

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 17 publications
1
15
0
8
Order By: Relevance
“…Research in the area of length measure learning trajectories has identified key moments we might reasonably expect among typical students in instruction (Barrett et al, 2012;Sarama & Clements, 2009;Sarama, Clements, Barrett, Van Dine, & McDonel, 2011;Szilágyi, Clements, & Sarama, 2013). For example, Steffe (1991) identified the conceptual ruler that we might expect as early as Grade 3 (about Age 8), which refers to one's ability to mentally iterate units even when not available along a particular object being measured.…”
Section: Implications Theoretical Implicationsmentioning
confidence: 99%
“…Research in the area of length measure learning trajectories has identified key moments we might reasonably expect among typical students in instruction (Barrett et al, 2012;Sarama & Clements, 2009;Sarama, Clements, Barrett, Van Dine, & McDonel, 2011;Szilágyi, Clements, & Sarama, 2013). For example, Steffe (1991) identified the conceptual ruler that we might expect as early as Grade 3 (about Age 8), which refers to one's ability to mentally iterate units even when not available along a particular object being measured.…”
Section: Implications Theoretical Implicationsmentioning
confidence: 99%
“…After administering the tasks for each interview, each video was reviewed to classify strategies along the learning trajectory. We report student progress along the length measurement tasks elsewhere Sarama, Clements, Barrett, Van Dine, & McDonel, 2011). In contrast, this report focuses on results for several tasks, looking for patterns of strategy usage across measures within students, not only for length, but also area and volume.…”
Section: Using Design Research In a Teaching Experiments And Hypothesementioning
confidence: 99%
“…Wilson, Sztajn, Edgington y Myers (2015) indican que la información sobre una trayectoria de aprendizaje de los contenidos matemáticos podría ayudar a los estudiantes para maestro a desarrollar su mirada profesional. Es decir, una trayectoria de aprendizaje puede proporcionar referencias al estudiante para maestro sobre cómo los conceptos matemáticos se desarrollan facilitando las conexiones entre los objetivos de aprendizaje y las actividades de enseñanza (Clements y Sarama, 2004;Sarama, Clements, Barrett, Van Dine y McDonel, 2011).…”
Section: Introduciónunclassified